2020
DOI: 10.1109/access.2020.3030778
|View full text |Cite
|
Sign up to set email alerts
|

A Ratio-Dependent Nonlinear Predator-Prey Model With Certain Dynamical Results

Abstract: In order to see the dynamics of prey-predator interaction, differential or difference equations are frequently used for modeling of such interactions. In present manuscript, we explore some qualitative aspects of two-dimensional ratio-dependent predator-prey model. Taking into account the non-overlapping generations for class of predator-prey system, a novel consistency preserving scheme is proposed. Our study reveals that the implemented discretization is bifurcation preserving. Some dynamical aspects includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Complexity Remark 3. Tassaddiq et al [35] used a nonstandard finite difference scheme and obtained the discrete ratio-dependent prey-predator model. ey showed that the considered system undergoes Neimark-Sacker bifurcation for larger values of the catchability coefficient.…”
Section: Case (I): Firstly Let Us Take the Parameter Values Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Complexity Remark 3. Tassaddiq et al [35] used a nonstandard finite difference scheme and obtained the discrete ratio-dependent prey-predator model. ey showed that the considered system undergoes Neimark-Sacker bifurcation for larger values of the catchability coefficient.…”
Section: Case (I): Firstly Let Us Take the Parameter Values Asmentioning
confidence: 99%
“…Furthermore, the author implemented three different types of control strategies to control the chaos. Moreover, for some interesting results related to bifurcation and chaos control in the predator-prey models, we refer the readers to [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we implement the hybrid control method for controlling the chaos caused by the period-doubling bifurcation and for controlling the Neimark-Sacker bifurcation in (4). Such strategies have been discussed elsewhere in [21,[33][34][35][36][37]. We assume the following controlled system corresponding to model (4):…”
Section: Chaos Controlmentioning
confidence: 99%
“…Moreover, oscillations emerge from supercritical or subcritical Hop bifurcation distributions under relatively low costs for fear. Therefore, the effect of fear can create multi-stability in predator-prey systems [38][39][40]. Mondal et al [41] showed the saddle node distribution, Hopf bifurcation, and Bogdanov-Takens bifurcation in an imprecise predator-prey system to show the fear effect and the existence of nonlinear harvesting of predators in an uncertain environment [41].…”
Section: Introductionmentioning
confidence: 99%